Determination of serum lithium: comparison between atomic emission and absorption spectrometry methods - Carlos Elielton do Espírito Santo; Teresa Maria de Jesus Ponte Carvalho (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: The therapeutic monitoring of lithium, through concentration measurements, is important for individual dose adjustment, as a marker of treatment adherence and to prevent poisoning and side effects. Objectives: Validate and compare two methods - atomic emission and atomic absorption - for the determination of lithium in serum samples. Methodology: Parameters such as specificity, precision, accuracy, limit of detection (LOD) and linearity were considered. The atomic absorption spectrometer was used, operating in either emission or absorption mode. For the quantitative comparison of 30 serum samples from patients with mood disorder treated with lithium, the results were submitted to Student's t-test, F-test and Pearson's correlation. Results: The limit of quantification (LOQ) was established as 0.05 mEq/l of lithium, and calibration curves were constructed in the range of 0.05-2 mEq/l of lithium, using aqueous standards. Sample preparation time was reduced, what is important in medical laboratory. Conclusion: Both methods were considered satisfactory, precise and accurate and can be adopted for lithium quantification. In the comparison of quantitative results in lithium-treated patients through statistical tests, no significant differences were observed. Therefore the methods for lithium quantification by flame atomic absorption spectrometry (FAAS) and flame atomic emission spectrometry (FAES) may be considered similar.